Rotator Cuff Injury and Repair - Fitzpatrick, Laura A.; Atinga, Angela; White, Lawrence; Henry, Patrick D.G.; Probyn, Linda (Seminars in Musculoskeletal Radiology, 2022)
Rotator cuff pathology is a commonly encountered clinical and radiologic entity that can manifest as tendinopathy or tearing. Magnetic resonance imaging (MRI) and ultrasonography offer similar sensitivity and specificity for the evaluation of the native rotator cuff, and the chosen modality may vary, depending on local practice and accessibility. MR arthrography is frequently used in the postoperative setting as a problem-solving tool. Key findings to include in the preoperative MRI report include the size and location of the tear, thickness of the tendon involved (partial versus full thickness), and overall tendon quality. The report should also address features associated with poor surgical outcomes, such as fatty atrophy, a decreased acromiohumeral interval, and evidence of rotator cuff arthropathy. Musculoskeletal radiologists should be familiar with the various surgical techniques and expected postoperative imaging appearance of rotator cuff repairs. Imaging also plays a role in identifying recurrent tearing, graft failure, hardware loosening, infection, and other complications.
Keywords: rotator cuff; tendinopathy; tear; postoperative rotator cuff